Individual factors that predict customer-orientation behaviour of Malaysian life insurance agents - Nor Azila Mohd Noor,; Azli Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2005)
The topic of customer-orientation has increasingly attracted interest in both academic marketing research and practice. One major factor which has been increasingly discussed as an important driver of a salespeople’s customerorientation is individual factor. In this study we examine the influence of three individual factors; namely, organizational commitment, self-monitoring and intrinsic motivation on salespeople customer-orientation behaviour. Data gathered from 445 life insurance agents were used to test the hypothesized relationship. The results suggest that organizational commitment and intrinsic motivation positively influence salespeople to perform customer-orientation behaviour in their selling activities. Self-monitoring however, was found to be unrelated to the adoption of customer-orientation behaviour. The academic and managerial implications of these findings are then discussed